2022
DOI: 10.6007/ijarbss/v12-i13/14144
|View full text |Cite
|
Sign up to set email alerts
|

Reduce, Reuse and Recycle (3r) Awareness Programme to Increase the Knowledge, Attitude and Practice on 3r among Primary School Students

Abstract: One of the issues of ineffective solid waste management may be attributable by human behaviour is lack of education and ineffectiveness of reduce, reuse and recycle (3R) awareness programmes, which the solution may lie in changing that behaviour. Therefore, a 3R programme was conducted to increase the knowledge, attitude and practice (KAP) on 3R among 155 primary school students recruited by systematic random sampling from year one to six at a selected school in Tumpat, Kelantan. A set of questionnaire was giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 7 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…Looking at the significant difference in the mean score knowledge between the two groups, this difference might be due to the 3R exposure given by the local authority or agency (SWCorp) who actively engaged with the school. The findings in our intervention study also reported significant increase in knowledge score (p=0.030) between before and after 3R programme (Anua et al, 2022b). This shows the importance of exposure of 3R program in increasing knowledge among students.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Looking at the significant difference in the mean score knowledge between the two groups, this difference might be due to the 3R exposure given by the local authority or agency (SWCorp) who actively engaged with the school. The findings in our intervention study also reported significant increase in knowledge score (p=0.030) between before and after 3R programme (Anua et al, 2022b). This shows the importance of exposure of 3R program in increasing knowledge among students.…”
Section: Resultssupporting
confidence: 77%
“…This study used self-administered and self-developed questionnaire which has been MYIPO copyrighted (LY2018004547) based on SWCorp (2017) module and published in previous studies (Anua et al, 2022a;2022b). The questionnaire consists of four parts.…”
Section: Study Instrumentmentioning
confidence: 99%
See 1 more Smart Citation